Kredit Usaha Rakyat (KUR) dalam Perspektif Hukum Pembangunan Ekonomi: Studi Kasus Keterbatasan Akses Modal bagi UMKM di Indonesia (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2026)
The People’s Business Credit (Kredit Usaha Rakyat, KUR) is a strategic program launched by the Government of Indonesia to expand access to financing for Micro, Small, and Medium Enterprises (MSMEs). The program offers subsidized interest rates and a non-collateral policy for loans below IDR 100 million. KUR is designed to support inclusive economic development by promoting the growth of MSMEs and creating more equitable economic opportunities. However, empirical evidence shows a significant gap between the legal objectives of the program and banking practices in the field. Disbursing banks, particularly state-owned banks (BUMN), often require hidden collateral and tend to prioritize existing borrowers over new ones. This misalignment undermines the program’s goals of expanding financial access to underserved entrepreneurs and fostering inclusive economic growth. This study applies a legal development economics approach to examine the divergence between public policy and the operational practices of banks. It highlights the implications of these discrepancies for achieving development objectives, MSME access to capital, and the broader principle of economic justice. The findings indicate the urgent need for regulatory harmonization, stronger banking supervision, and legally grounded financial inclusion strategies to ensure that KUR functions effectively as a catalyst for equitable and sustainable economic growth.